Penguatan Modal Sosial pada Penataan Kawasan Kumuh Kampung Gumelem di Era Pandemi Covid-19 - Inayati Safitri; N. Yuliastuti; M. Maryono (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Safitri I, Yuliastuti N, Maryono M. 2020. Strengthening Social capital on the arrangement of the gumelem village slum area in covid-19 pandemic. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Gumelem Village is one of the slum areas in the Pemalang Regency, Central Java Province. This area has characteristics such as high population density, narrow neighborhood roads, the location of the houses that are coincided, the house is narrow and the house is inhabited by several families, and does not have a private toilet. The formation of slum settlements is an obstacle in regional development efforts. Therefore, efforts to organize areas are needed. Besides, in the current pandemic era, slum settlements are among the most vulnerable to the danger of spreading the virus because of their high density, low access to drinking water, and proper sanitation for health. This research uses the Participatory Research Appraisal (PRA) method to ensure the active involvement of the community who is the target group and place the community as the subject in the activation process. The results showed that social capital in the community and the government was not sufficiently strong to implement. For this reason, the right strategy is needed to organize the slum area of the Gumelem village in the era of the Covid-19 pandemic.